Local public health under threat: Harassment faced by local health department leaders during the COVID-19 pandemic - Jordan Royster; Jack A. Meyer; Margaret C. Cunningham; Kellie Hall; Krishna Patel; Timothy C. McCall; Aaron A. Alford (Elsevier, 2024)
Background: Prior to the COVID-19 pandemic, local health departments (LHDs) faced several challenges including underfunding and understaffing. COVID-19 exacerbated these challenges and introduced new ones, including harassment of the agency, staff, and leadership. The objective of this study was to qualitatively understand the experiences and impact of harassment faced by LHDs during the pandemic and provide recommendations to prevent future harassment. Study design: A qualitative study was conducted utilizing focus groups for data collection. Methods: LHDs were sampled from the 2022 National Profile of Local Health Departments (Profile) study to ensure diversity in LHD size. Four virtual focus groups were conducted in Fall 2022 with a total of 16 LHD leaders surveyed in Profile, who were still in their positions. Focus group transcripts were then coded by two independent coders and analyzed using thematic analysis. Findings: Four common domains arose from the data: aggravating factors of harassment, content and formats of harassment, protective factors, and effects on individuals and on the workforce. Conclusion: Findings suggest that harassment was pervasive with many forms and impacts on the LHD leaders and workforce overall. Recommendations are proposed for the local as well as federal partners because the public health system is threatened without immediate, substantial, and coordinated solutions to address harassment and offer protection.